Novel Polymeric Resin for Solid Phase Extraction and Determination of Lead in Waters - Karaaslan, Nagihan M.; Senkal, B. Filiz; Cengiz, Emine; Yaman, Mehmet (Wiley-Blackwell, 2010)
Interest in preconcentration techniques for the determination of metals at ultratrace levels still continues increasingly because of some disadvantages of flameless atomic absorption spectrometry and the high costs of other sensitive methods in compared to flame atomic absorption spectrometry (FAAS) Among preconcentration techniques solid phase extraction is the most popular because of a number of advantages In this work thiol-containing sulfonamide resin was synthesized characterized and applied as a new sorption material for solid phase extraction and determination of lead in natural water samples The optimization of experimental conditions was performed using the parameters including pH contact time and volumes of initial and elution solutions After preconcentration procedure FAAS was used for determinations The synthesized resin exhibits the superiority in compared to the other adsorption reagents because of the fact that there is no necessity of any complexing reagent as well as high sorption capacity Consequently 280 fold improvement in the sensitivity of analytical scheme was achieved by combining the slotted tube atom trap atomic absorption spectrometry (STAT FAAS) and the developed preconcentration method The limit of detection was found to be 0 15 ng mL(-1) The Pb2+ concentrations in the studied water samples were found to be in the range of 0 9-6 7 ng mL(-1)
Keywords: Atomic absorption; Lead Preconcentration; Thiol containing sulfonamide resin; Water